Highly sensitive and fast responding CO sensor based on Co3O4 nanorods - Patil, Dewyani; Patil, Pradip; Subramanian, Vijayanand; Joy, Pattayil Alias; Potdar, Hari S. (Talanta, 2010)
Co3O4 nanorods (diameters similar to 6-8 nm and lengths similar to 20-30 nm) were synthesized for the first time through a simple co-precipitation/digestion method by calcination of cobalt hydroxyl carbonate in air and their CO gas sensing properties were investigated. The Co3O4 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 6.55-50 ppm CO gas at 250 degrees C), extremely rapid response (similar to 3-4s), fast recovery (similar to 5-6s), excellent repeatability, good selectivity and lower operating temperature (similar to 250 degrees C). Furthermore, the Co3O4 nanorods are able to detect up to 5 ppm for CO with reasonable sensitivity (similar to 3.32) at an operating temperature 250 degrees C and they can be reliably used to monitor the concentration of CO over the range (5-50 ppm). The experimental results clearly demonstrate the potential of using the Co3O4 nanorods as sensing material in the fabrication of CO sensors. Plausible CO sensing mechanism of the Co3O4 nanorods is also discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CO sensor; Co3O4 nanorods; HRTEM; Semiconductor gas sensors; XPS; XRD

Highly sensitive and selective LPG sensor based on alpha-Fe2O3 nanorods - Patil, Dewyani; Patil, Virendra; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
The alpha-Fe2O3 nanorods were successfully synthesized without any templates by calcining the alpha-FeOOH precursor in air at 300 degrees C for 2 h and their LPG sensing characteristics were investigated. The alpha-FeOOH precursor was prepared through a simple and low cost wet chemical route at low temperature (40 degrees C) using FeSO4 center dot 7H(2)O and CH3COONa as starting materials. The formation of alpha-FeOOH precursor and its topotactic transformation to alpha-Fe2O3 upon calcination was confirmed by X-ray diffraction measurement (XRD). X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. The alpha-Fe2O3 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 1746-50 ppm LPG at 300 degrees C), extremely rapid response (similar to 3-4 s), relatively slow recovery (similar to 8-9 min), excellent repeatability, good selectivity and lower operating temperature (similar to 300 degrees C). Furthermore, the alpha-Fe2O3 nanorods are able to detect up to 5 ppm for LPG with reasonable response (similar to 15) at the operating temperature of 300 degrees C and they can be reliably used to monitor the concentration of LPG over the range (5-60 ppm). The experimental results clearly demonstrate the potential of using the alpha-Fe2O3 nanorods as sensing material in the fabrication of LPG sensors. Plausible LP G sensing mechanism of the alpha-Fe2O3 nanorods is also discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alpha-Fe2O3 nanorods; FESEM; LPG sensor; Semiconductor gas sensors; TEM; XPS; XRD

Nanostructured spinet ZnCo2O4 for the detection of LPG - Vijayanand, Subramanian; Joy, Pattayil Alias; Potdar, Hari S.; Patil, Dewyani; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
Nanostrucutred spinel ZnCo2O4 (similar to 26-30 nm) was synthesized by calcining the mixed precursor (consisting of cobalt hydroxyl carbonate and zinc hydroxyl carbonate) in air at 600 degrees C for 5 h. The mixed precursor was prepared through a low cost and simple co-precipitation/digestion method. The transformation of the mixed precursor into nanostructured spinel ZnCO2O4 upon calcinations was confirmed by X-ray diffraction (XRD) measurement, thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) and high resolution transmission electron microscopy (HRTEM). To demonstrate the potential applicability of ZnCo2O4 spinel in the fabrication of gas sensors, its LPG sensing characteristics were systematically investigated. The ZnCo2O4 spinel exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 72-50 ppm LPG gas at 350 degrees C), response time (similar to 85-90 s), recovery time (similar to 75-80 s), excellent repeatability, good selectivity and relatively lower operating temperature (similar to 350 degrees C). The experimental results demonstrated that the nanostructured spinel ZnCo2O4 is a very promising material for the fabrication of LPG sensors with good sensing characteristics. Plausible LPG sensing mechanism is also discussed. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: HRTEM; LPG sensor; Nanostructured ZnCo2O4; Semiconductor gas sensors; XPS